Common law and Enlightenment in England, 1689-1750 / Julia Rudolph. - Rudolph, Julia, 1962- (Boydell & Brewer, 2013)
This book explores how English legal culture, deeply imbued with the ideas and practices of common law, engaged with the new intellectual, institutional and cultural changes of the Enlightenment. It argues that common law survived as an important part of English legal culture because it was able to meet the various challenges posed by Enlightenment rationalism and civic and commercial discourse. Drawing on works of jurisprudence, legal histories, manuals of law and notebooks of legal practice, and looking in detail at four pivotal, widely-discussed cases, the book illuminates the ways in which common law custom and tradition continued to be valued foundations for the authority of law, even during a period of political change, commercial growth and philosophical rationalism. Exploring the challenges to and adaptations within common law thinking in England in the late seventeenth and early eighteenth centuries, the book reveals that the common law played a much wider role beyond the legal world in shaping Enlightenment concepts. JULIA RUDOLPH is Associate Professor of History at North Carolina State University. She is the author of 'Revolution by Degrees: James Tyrrell and Whig Political Thought in the Late Seventeenth Century' (Palgrave Macmillan, 2002), and of various articles on gender, crime, and the history of the book in early modern England. She has also edited a collection of theoretical and interdisciplinary essays entitled 'History and Nation' (Bucknell University Press, 2006).